2009
DOI: 10.1631/jzus.b0820238
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induces apoptosis through the mitochondria-mediated apoptotic pathway in HT-29 cells

Abstract: Abstract:Objective: To investigate the effects of curcumin on release of cytochrome c and expressions of Bcl-2, Bax, Bad, Bcl-xL, caspase-3, poly ADP-ribose polymerase (PARP), and survivin of HT-29 cells. Methods: HT-29 cells were treated with curcumin (0~80 μmol/L) for 24 h. The release of cytochrome c from the mitochondria and the apoptosis-related proteins Bax, Bcl-2, Bcl-xL, Bad, caspase-3, PARP, and survivin were determined by Western blot analysis and their mRNA expressions by reverse transcriptase-polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 38 publications
3
54
0
Order By: Relevance
“…colorectal cancer is one of the leading causes of cancer-related death in Western countries, and its incidence is increasing rapidly in asia (1,2). Surgical resection followed by adjuvant chemotherapy has been considered the optimal treatment approach for patients with colon cancer (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…colorectal cancer is one of the leading causes of cancer-related death in Western countries, and its incidence is increasing rapidly in asia (1,2). Surgical resection followed by adjuvant chemotherapy has been considered the optimal treatment approach for patients with colon cancer (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Bcl-2 and Bcl-xl inhibit apoptosis while Bax and Bad promote apoptosis (32). It is reported that a number of traditional Chinese medicines exhibit their antitumor effects by simultaneous upregulation of Bax and Bad and downregulation of Bcl-2 and Bcl-xl (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…The transformation of fibroblasts into myofibroblasts is stimulated by TGFβ1, which is found in high levels in burns and scalds (Heng 2011, Tredget et al 2006. The formation of myofibroblasts is also enhanced by wound tension, infection, deep wounds (Dunkin et al 2007, Wang et al 2008) and an inherited keloidal tendency (Lee et al 1999, Abdou et al 2011, Heng 2011. It is noteworthy that hypertrophic scarring is usually not observed in embryos and fetuses , Martin 1997, Ferguson and O'Kane 2004, in whom TGFβ1 is only expressed transiently and at low levels (Martin et al 1993, Martin 1997, Whitby and Ferguson 1991 with resulting absence of myofibroblast conversion (Estes et al 1994, Armstrong andFerguson 1995).…”
Section: Role Of Fibroblasts and Myofibroblasts In Hypertrophic Scarringmentioning
confidence: 99%